Online Learning a Rude Wake-Up Call on Inclusive Education in Zimbabwean University Context: 3rd International Multidisciplinary Information Technology and Engineering Conference (IMITEC) Windhoek, Namibia 23-25 November 2021 - Rodney Tichaona Munemo; Plaxcedes Gundidza (IEEE, 2023)
The Coronavirus pandemic (COVID-19) has brought changes to teaching practices in Zimbabwean Universities. The ensuing rapid digitalization of learning has noticeable impacts on access to education for students with different abilities. The use of Learning Management Systems (LMS) such as Google Classroom, Google Meet, Moodle among others creates a digital divide between students who are techsavvy and those who are technophobic. Furthermore, it appears that online learning is exclusive to some students and tends to view all students as the same. This is problematic, given that some students face diverse challenges ranging from limited or compromised access to internet networks and affordability of Information Communication Technology (ICT) gadgets for participating in online classes. This study provides a detailed contemporary view of the practices associated with electronic learning and the challenges faced by students during online classes. Study findings revealed some proactive measures taken by the university authorities and teaching staff to promote inclusive education and assessment. Study respondents highlighted the challenges of internet connectivity, affordability of gadgets and data needed for learning, power outages, different levels of proficiency in using the University’s recommended Learning Management System.